2019
DOI: 10.1177/1120672119872606
|View full text |Cite
|
Sign up to set email alerts
|

Pattern electroretinogram changes in patients with primary open-angle glaucoma in correlation with visual field and optical coherence tomography changes

Abstract: Purpose: To study the pattern electroretinogram changes in primary open-angle glaucoma patients in correlation with visual field changes and optical coherence tomography measurements of retinal nerve fiber layer thickness in the peripapillary region in an attempt to evaluate the clinical value of pattern electroretinogram as an objective test of functional deficit in glaucoma. Patients and Methods: The study included 81 eyes of 81 participants: 50 primary open-angle glaucoma patients, 16 primary open-angle gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In our present study, we observed mfPhNR/b-wave ratios to be significantly correlated with both PERG 0.8° amplitude and PERG ratio (r 2 = 0.11, P = 0.02). This supports the view that both measures they reflect similar damage sites and mechanisms, which is further corroborated by the cross-modal correlations of the electrophysiological measures with functional and anatomical measures we observed in accordance with previous conventional PhNR studies(Viswanathan et al 2001; Machida et al 2008; Kirkiewicz et al 2016), PERG studies(Parisi et al 2001; Toffoli et al 2002; Elgohary et al 2019) and another mfPhNR study(Kato et al 2015). In fact, the observed pRNFL changes were a predictor for both mfPhNR/b-wave ratio and PERG 0.8° amplitude.…”
Section: Discussionsupporting
confidence: 92%
“…In our present study, we observed mfPhNR/b-wave ratios to be significantly correlated with both PERG 0.8° amplitude and PERG ratio (r 2 = 0.11, P = 0.02). This supports the view that both measures they reflect similar damage sites and mechanisms, which is further corroborated by the cross-modal correlations of the electrophysiological measures with functional and anatomical measures we observed in accordance with previous conventional PhNR studies(Viswanathan et al 2001; Machida et al 2008; Kirkiewicz et al 2016), PERG studies(Parisi et al 2001; Toffoli et al 2002; Elgohary et al 2019) and another mfPhNR study(Kato et al 2015). In fact, the observed pRNFL changes were a predictor for both mfPhNR/b-wave ratio and PERG 0.8° amplitude.…”
Section: Discussionsupporting
confidence: 92%
“…Between Groups (II) and (III), P50 latency and N95 (latency, amplitude) did not differ substantially. In the same line, Elgohary et al 27 found that P50 peak time varied significantly between the GS and POAG groups, whereas N95 peak time varied significantly between the normal and POAG groups. Between the GS and POAG groups, there was a substantial difference in the PERG N95 amplitude.…”
Section: Discussionmentioning
confidence: 79%
“…Cross-sectional studies reported variable, usually weak to moderate correlation between PERG/PhNR and SAP/structural parameters [30][31][32][33][34] or even lack of correlation [25,35]. Different stages of disease (e.g.…”
Section: Discussionmentioning
confidence: 99%